Analisis Pembiayaan Mudharabah, Pembiayaan Musyarakah, Dan Pembiayaan Murabahah Terhadap Kinerja Keuangan - Putri, Indah Prihandini Utami; Safira, Safira (Universitas Mercu Buana, 2019)
This study aims to examine the effect of mudharabah financing, musyarakah financing, and murabahah financing on financial performance (ROA). This research was conducted at the Sharia People's Financing Bank (BPRS) registered with the Financial Services Authority (OJK). Samples were taken using purposive sampling method. The total sample in this study were 4 companies. Data analysis method uses multiple linear regression analysis. The results of this study indicate that mudharabah financing, musyarakah financing, and murabahah financing have a significant effect on financial performance which is proxied by ROA.